2013
DOI: 10.1016/j.it.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin in the immune system: ins and outs

Abstract: Calreticulin is a calcium-binding chaperone that has several functions in the immune response. In the endoplasmic reticulum (ER), calreticulin facilitates the folding of major histocompatibility complex (MHC) class I molecules and their assembly factor tapasin, thereby influencing antigen presentation to cytotoxic T cells. Although calreticulin is normally ER-resident, it is found at the cell surface of living cancer cells and dying cells. Here, calreticulin promotes cellular phagocytic uptake. In tumor vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 77 publications
(183 reference statements)
2
139
0
Order By: Relevance
“…Therefore, it is possible that the glycan-independent interactions described here could also mediate interactions between calreticulin and proteins in cellular compartments outside the ER (reviewed in Ref. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that the glycan-independent interactions described here could also mediate interactions between calreticulin and proteins in cellular compartments outside the ER (reviewed in Ref. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that cytokine-mediated UPR could influence post-translational modification of proteins, leading to production and presentation of potential autoantigens. It was previously shown that ER calcium depletion drives the translocation of ER-resident proteins BiP, GRP94, and calreticulin in the plasma membrane (Peters & Raghavan 2011), which may have pro-or anti-inflammatory outcomes depending on the protein and cellular context (Panayi & Corrigall 2006, Peters & Raghavan 2011, Raghavan et al 2013 (Rondas et al 2015). Interestingly, proinflammatory cytokines, but not ER stressors, induced BiP citrullination in INS-1E cells (Rondas et al 2015).…”
Section: Er Stress and Antigen Presentationmentioning
confidence: 95%
“…5,16,17 The current literature suggests that the molecular mechanisms accounting for CRT exposure are highly complex and require further in-depth analysis. 17,19,20 Extrareticular CRT is not only of immunological relevance. Indeed, CRT has been detected at the surface of capacitated spermatocytes and oocytes, 21,22 and circumstantial evidence indicates that CRT contributes to the fusion of gametes and fertility, both in mammals and in nematodes.…”
mentioning
confidence: 99%